Body stoichiometry of heterotrophs: Assessing drivers of interspecific variations in elemental composition. Issue 4 (9th February 2021) - Andrieux, Benjamin; Signor, Juliette; Guillou, Vincent; Danger, Michael; Jabot, Franck
Abstract: Aim: The aim was to document how body stoichiometry of heterotrophs varies globally and to assess phylogenetic, trophic, habitat and body mass drivers of this interspecific variation in elemental composition, focusing on carbon (C), nitrogen (N) and phosphorus (P). Location: World‐wide. Time period: 1930–2019. Major taxa studied: Amphibians, fishes (Actinopterygii), invertebrates, mammals, microbes and sauropsids (birds and reptiles). Methods: We compiled from the scientific literature a global database of body elemental composition of heterotrophs in marine, freshwater and terrestrial realms. We used model selection and ANCOVAs to investigate the proportion of variance in elemental composition explained by taxonomic groups, diet, habitat and body mass. We assessed the phylogenetic signal in body stoichiometry using Blomberg's K and Pagel's λ statistics. We assessed the phylogenetic structure of interspecific variation in body stoichiometry using mixed models, with nested taxonomic levels as random factors. We finally assessed the covariations in elemental composition. Results: Our database gathered 31, 371 observations on 1, 512 species. Body elemental composition was widely variable among species, with the four assessed drivers contributing significantly to this variation. Taxonomic group was the strongest contributor to interspecific variance for the stoichiometric traits studied, followed by habitat, diet and body mass. More precisely, C, N and P contents and C:N ratio were generally structured among classes, whereas the largest variations in C:P and N:P ratios were among families. This resulted in a significant but relatively modest phylogenetic signal. Finally, we found significant covariation among the three body elemental contents, resulting in taxonomic group‐specific C:N:P spectra. Main conclusions: Our global synthesis of body stoichiometry of heterotrophs revealed a strong interspecific variability that was only modestly explained by the species attributes investigated (body mass, habitat and diet). It also revealed that this taxonomically structured residual variation in body stoichiometry seemed to be constrained along taxonomic group‐specific elemental spectra.